Estudo de prevalência e incidência da associação entre insônia e apneia obstrutiva do sono (COMISA) em uma amostra populacional - Luciano, Ygor de Matos [UNIFESP] (2024)
Introduction: Obstructive sleep apnea (OSA) and insomnia represent the most prevalent sleep disorders, negatively affecting physical and mental health. Both insomnia and OSA have great clinical and social relevance. More recently, emphasis has been placed on discussing the simultaneous presence of both diseases, known as COMISA – comorbid insomnia and sleep apnea. In this sense, the study of prevalence and incidence is essential to establish the first advances regarding the developments of this phenomenon. Objective: To investigate the prevalence and incidence of COMISA based on the Sleep Epidemiological Study of the city of São Paulo – EPISONO. Methods: EPISONO: the 3rd edition (2007) and the follow-up study of the 3rd edition (2015) were used as the basis for this project. Insomnia symptoms were assessed using the insomnia severity index (ISI), categorizing participants into the following severity levels: normal (0-7), mild/subclinical (8-14), moderate (12-21), or severe (22-28). OSA was diagnosed based on the apnea and hypopnea index (AHI) obtained through polysomnography, considering the following levels of severity: mild (5-15, as long as it is associated with symptoms), moderate (5-15) or severe (>15). Results: The final sample included 585 participants with valid ISI and AHI data in both editions. In 2007, the prevalence of COMISA in the general population was 17.64% [95%CI=15.14%-20.14%]. After 8 years, the prevalence of COMISA increased by 5.31%, reaching 22.95% [95%CI=19.80%-26.10%]. The incidence of COMISA was calculated only in 2015, based on participants who had not presented this condition in 2007. The overall incidence of COMISA in the sample was 16.67% [95%CI=13.75%-19.59%]. Conclusion: The prevalence of COMISA among the general population is high and shows a significant increase over an 8-year follow-up. The incidence of COMISA is also high, affecting approximately 1/6 of people who did not have this condition at the first evaluation. Taken together, these data corroborate the importance of the association between OSA and insomnia in sleep medicine.